2009
DOI: 10.1080/13803390902889606
|View full text |Cite
|
Sign up to set email alerts
|

The California Verbal Learning Test and other standard clinical neuropsychological tests to predict conversion from mild memory impairment to dementia

Abstract: This study describes the neuropsychological assessment of 34 patients with questionable Alzheimer's disease (QAD) followed up for 3 years. Several measures were selected from the California Verbal Learning Test (CVLT) and compared to other cognitive tasks to assess the best neuropsychological indices for (a) detecting early memory impairment in QAD and (b) predicting conversion to AD. Concerning detection, the results indicated that a recall measure depending on semantic categorization (short-delay cued recall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 42 publications
1
37
0
Order By: Relevance
“…NOC participants were healthy UK-ADC cohort volunteers (n = 4) or referrals to the memory clinic for evaluation who did not receive a clinical diagnosis and were considered NOC based on criteria listed below (n = 14). In keeping with contemporary clinical criteria (Albert et al, 2011; Arsenault-Lapierre et al, 2011; Lekeu et al, 2010; Reid & Maclullich, 2006), aMCI was indicated by A) absence of dementia, B) absence of cognitive, clinical, or behavioral symptoms consistent with sources of non-amnestic cognitive impairment, and C) objective memory impairment evidenced by performance more than 1.5 standard deviations below age-standardized normal values on at least one of several memory measures including Wechsler Memory Scale Logical Memory (WMS-R), the California Verbal Learning Test (CVLT-II), and the Benton Visual Retention Test (BVRT-5, Forms C & D). AD was diagnosed using Alzheimer’s Disease Dementia Workgroup criteria, which hold, briefly, that insidious-onset dementia is present in the absence of another psychiatric or neurological condition (McKhann et al, 2011).…”
Section: Methodsmentioning
confidence: 92%
“…NOC participants were healthy UK-ADC cohort volunteers (n = 4) or referrals to the memory clinic for evaluation who did not receive a clinical diagnosis and were considered NOC based on criteria listed below (n = 14). In keeping with contemporary clinical criteria (Albert et al, 2011; Arsenault-Lapierre et al, 2011; Lekeu et al, 2010; Reid & Maclullich, 2006), aMCI was indicated by A) absence of dementia, B) absence of cognitive, clinical, or behavioral symptoms consistent with sources of non-amnestic cognitive impairment, and C) objective memory impairment evidenced by performance more than 1.5 standard deviations below age-standardized normal values on at least one of several memory measures including Wechsler Memory Scale Logical Memory (WMS-R), the California Verbal Learning Test (CVLT-II), and the Benton Visual Retention Test (BVRT-5, Forms C & D). AD was diagnosed using Alzheimer’s Disease Dementia Workgroup criteria, which hold, briefly, that insidious-onset dementia is present in the absence of another psychiatric or neurological condition (McKhann et al, 2011).…”
Section: Methodsmentioning
confidence: 92%
“…In one study, the Rey Auditory Verbal Learning Test (RAVLT) short delayed recall was the most significant neuropsychological test in 5- and 10-year follow-ups to emerge as a predictor of AD (17). In another, short-delay cued recall score on the CVLT(18) was the neuropsychological test that best discriminated stable and declining questionable AD subjects from controls (19). In yet another study, both the total learning and delayed recall scores of the RAVLT predicted progression to AD and classified between MCI and normal aging (20), and another group of investigators found long delayed total recall (CVLT free and cued) combined with Mini-Mental State Examination to be the best predictor of MCI progression onto AD (21).…”
Section: Discussionmentioning
confidence: 99%
“…Third, as a novel memory task, we have previously found it to have large practice effects in older adults and these practice effects have predicted future cognitive functioning in prior studies 20, 23, 24 . Finally, visual spatial tasks, including those assessing memory, appear to be sensitive to various dementing conditions 3235 . Although alternate forms are available for the BVMT-R, they were not used in this study to maximize practice effects.…”
Section: Methodsmentioning
confidence: 99%